Management of Acacia species seed banks in the Table Mountain National Park, Cape Peninsula, South Africa - Jasson, Rene (Stellenbosch : University of Stellenbosch, 2008)
Thesis (MScAgric (Conservation Ecology and Entomology)--University of Stellenbosch, 2005.